Strategi Pendidikan Nilai Sebagai Pembentuk Kepribadian Siswa Di Sekolah - Rinita Rosalinda Dewi; Mufid Hidayat; Cik Suabuana (Universitas Kanjuruhan Malang, 2021)
Value education is a conscious and planned effort to help students recognize the values that must be used as a guide in behaving and behaving in everyday life. The purpose of this research was to determine the value education strategy as forming the personality of students in schools, especially at the elementary school level. SDN Nagreg 04 is one of the elementary schools that instill value education as a way of shaping the personality of students so that they become personal benefits for others. This research uses descriptive qualitative methods and uses data collection techniques through observation, interviews, and documentation studies. Based on research results show that the value education strategy as forming the personality of students in schools can be started from the curriculum and tools such as syllabus and lesson plans, plan various programs that can support the process of value education to students, integrated with teaching and learning activities, and through collaboration between schools, parents, and society.